2001
DOI: 10.1111/j.1469-7793.2001.0031g.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of elementary mechanosensitive Ca2+‐influx events, Ca2+ spots, in bovine lens epithelial cells

Abstract: 6. From these results, we propose that the Ca 2+ spot is an elementary Ca 2+ -influx event through MS channels directly coupled with the first step in mechanoreception In addition, our results strongly suggest that LPA functions as an endogenous factor affecting mechanotransduction systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Fluorescence images of fluo 4 were collected by use of a real-time confocal imaging system as previously described. 26 With use of the imaging system, fluo 4 images with 60ϫ60 pixels with x-y resolution of 1.3 to 2 m per pixel were acquired with 55-to 110-ms exposure at 32°C. The intensity of fluo 4 fluorescence for each region of interest was divided by the averaged resting fluorescence intensity of Ͼ10 frames before stimulation of the same region, after which the background fluorescence was subtracted.…”
Section: Confocal Imaging Of [Ca 2؉ ] I With Fluomentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence images of fluo 4 were collected by use of a real-time confocal imaging system as previously described. 26 With use of the imaging system, fluo 4 images with 60ϫ60 pixels with x-y resolution of 1.3 to 2 m per pixel were acquired with 55-to 110-ms exposure at 32°C. The intensity of fluo 4 fluorescence for each region of interest was divided by the averaged resting fluorescence intensity of Ͼ10 frames before stimulation of the same region, after which the background fluorescence was subtracted.…”
Section: Confocal Imaging Of [Ca 2؉ ] I With Fluomentioning
confidence: 99%
“…25 In addition, using real-time confocal microscopy, we recently demonstrated that LPA enhanced the mechanical stress-induced local increase in [Ca 2ϩ ] i , termed Ca 2ϩ spots, in cultured lens epithelial cells. 26 Considering those facts, we have proposed that the Ca 2ϩ spot is an elementary Ca 2ϩ -influx event through MS ion channels that is directly coupled with the first step in mechanoreception, and we have suggested that LPA functions as an endogenous factor affecting mechanotransduction systems.…”
mentioning
confidence: 99%
“…As presented in Fig. 3B, the spatiotemporal properties were similar to those of Ca 2+ spots observed in lens epithelial cells (16). In addition, the pharmacological properties of the local increase in [Ca 2+ ]i showed that the response was due to Ca 2+ influx through MS channels (13) …”
Section: +mentioning
confidence: 51%
“…This mechanical stress did not affect acquisition of fluorescent images and induced a reproducible response; however, a combination of both flow and pressure stress may have been involved. Estimated intensities of the shear and the pressure stresses occurred within physiological range (16 ]i in the presence of LPA in ileum smooth muscle cells (7), lung epithelial cells (10) and lens epithelial cells (11,16) (Fig. 1A).…”
Section: +mentioning
confidence: 99%
“…-influx event through mechanosensitive channels directly coupled with the initial step in mechanotransduction in cultured endothelial (4 -6) and cultured lens epithelial cells (6,7). The Ca 2+ spots, which develop sporadically, exhibit a spatiotemporal pattern distinct from Ca 2+ sparks, the elementary [Ca…”
Section: +mentioning
confidence: 99%